The clinical-immunological analysis of a specific and combined immunotherapy of patients with cervical cancer - D. K. Kenbayeva; A. F. Lazarev (Опухоли женской репродуктивной системы)
Research objective is the comparative assessment of efficiency of two various ways of an immunotherapy of patients with cervical cancer. 57 patients with cervical cancer, the III stages, distributed on 3 groups – combined radiotherapy, a combination of a radiotherapy and specific immunotherapy, and also a radiotherapy, specific and adaptive immunotherapy are surveyed. Clinical efficiency of treatment was estimated by means of primary tumor regression and 3-year survival rate. The scheme of combined immunotherapy was shown to possess the most clinical efficiency. Positive dynamics of cell immunity indicators was accompanied to clinical efficiency of treatment.